2009
DOI: 10.1177/112067210901900416
|View full text |Cite
|
Sign up to set email alerts
|

Can an Intraoperative Bevacizumab Injection Prevent Recurrent Postvitrectomy Diabetic Vitreous Hemorrhage?

Abstract: The study suggests that intravitreal bevacizumab injection cannot prevent rebleeding in eyes undergoing pars plana vitrectomy for treatment of diabetic vitreous hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
(11 reference statements)
2
30
1
Order By: Relevance
“…As almost all residual bevacizumab in the vitreous may be washed out during vitrectomy, it would be unavailable to inhibit remaining or future fibrovascular growth [18,29]. In contrast to our results, one study reported that intraoperative bevacizumab injection cannot prevent rebleeding in eyes undergoing pars plana vitrectomy for treatment of diabetic vitreous hemorrhage [35]. However, this study has several limitations such as limited number of cases and the lack of a control group, while our study included a control group.…”
Section: Discussioncontrasting
confidence: 62%
“…As almost all residual bevacizumab in the vitreous may be washed out during vitrectomy, it would be unavailable to inhibit remaining or future fibrovascular growth [18,29]. In contrast to our results, one study reported that intraoperative bevacizumab injection cannot prevent rebleeding in eyes undergoing pars plana vitrectomy for treatment of diabetic vitreous hemorrhage [35]. However, this study has several limitations such as limited number of cases and the lack of a control group, while our study included a control group.…”
Section: Discussioncontrasting
confidence: 62%
“…Although preoperative bevacizumab is eliminated from the vitreous with vitrectomy, its action may be prolonged by tissue penetration, since the presence of the drug in the choroid and inner retina one day after intravitreal administration has been demonstrated, continuing to be detectable 14 days after its use (34) . The intraoperative use of bevacizumab in vitrectomy has also been reported (32) . In the study by Romano et al (32) , a prospective case series in which 2.5 mg bevacizumab was administered at the end of pars plana vitrectomy, the incidence of postoperative vitreous hemorrhage did not seem to be lower than the values reported in the literature.…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pmentioning
confidence: 99%
“…The intraoperative use of bevacizumab in vitrectomy has also been reported (32) . In the study by Romano et al (32) , a prospective case series in which 2.5 mg bevacizumab was administered at the end of pars plana vitrectomy, the incidence of postoperative vitreous hemorrhage did not seem to be lower than the values reported in the literature. A possible explanation for this fact is that inhibition of VEGF during the immediate postoperative period may compromise vascular regeneration and favor re-bleeding (28) .…”
Section: Preoperative Administration Of Anti-vegf Drugs Before Pars Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the vascularity of neovascular fibrovascular tissue can potentially reduce bleeding intraoperatively and thus facilitate the vitrectomy procedure. Recently, intravitreal bevacizumab has been suggested as a useful preoperative adjunct for cases with severe active PDR complicated with TRDs [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and postoperatively for recurrent vitreous hemorrhage [19,20] . The aim of this study was to evaluate the effectiveness of intravitreal injection of bevacizumab as a preoperative adjunct in order to reduce potential intra-and postoperative bleeding, facilitate surgery and improve visual outcomes for patients with severe PDR.…”
Section: Introductionmentioning
confidence: 99%